Sleep Disorders in Four Patients With Myotonic Dystrophy Type 1 - Urata, Yuka; Nakamura, Masayuki; Shiokawa, Nari; Yasuniwa, Aiko; Takamori, Nagisa; Imamura, Kensuke; Hayashi, Takehiro; Ishizuka, Takanori; Kasugai, Motofumi; Sano, Akira (Frontiers in Neurology, 2020)
Sleep disturbances such as excessive daytime sleepiness, central and obstructive sleep apneas, restless legs syndrome, and rapid-eye-movement sleep dysregulation are prominent in patients with myotonic dystrophy type 1 (DM1). Mild intellectual deficits are presented in many patients with DM1. In addition, psychosocial issues caused by neuropsychiatric symptoms are a clinical problem. We herein present the cases of four DM1 patients with sleep disturbances and neuropsychiatric symptoms in preceding stage of clinically significant muscle symptoms. One of the cases exhibited sleep disorder and neuropsychiatric symptoms before electromyography showed myotonic discharge, suggesting that careful follow-up is also important. Patients 1 and 2 were first referred to our department due to daytime sleepiness. Patients 3 and 4 were objectively suffering from daytime sleepiness of which they were not subjectively aware. Patients 1, 3, and 4 obtained high apnea hypopnea index (AHI) scores which reflected central and/or obstructive apnea, whereas patient 2 had an AHI score of zero. The daytime CSF orexin levels of all patients ranged from the normal lower limit to low, although they were not as low as those observed in narcolepsy with typical cataplexy. Neuropsychological tests of patient 1 and 2 showed frontal lobe dysfunction. Patient 3 and 4 were diagnosed as mild intellectual disability and autism spectrum disorder, respectively. All patients exhibited indifference towards their own symptoms, which may have resulted from the cognitive decline caused by DM1. Based on family history and/or neurological findings such as myotonia, we suspected DM1 as the cause of their sleep disturbances. Molecular analysis using the triplet repeat-primed polymerase chain reaction (TP-PCR) method and/or Southern blotting, which provided a genetic confirmation of the diagnosis of DM1, were performed. These clinical features of sleep disturbances were unrelated to the length of CTG repeats, and are caused by unknown molecular mechanisms. Clinicians should take into account that multisystem involvement in DM1 is hugely variable and thus, a disabling sleep disorder could overshadow muscle impairment in DM1 patients.